Шляхи вдосконалення трудового законодавства, норми якого регулюють питання відшкодування шкоди - Мельник, В. В.; Melnyk, V. V. (Юридична наука. - 2020. - № 2, т. 2. - С. 175-183, 2020)
Констатована наявність ряду суттєвих проблем у законодавстві, яке регламентує відшкодування шкоди у трудовому праві, що негативним чином позначаються на стані законності у сфері трудових відносин та ефективності захисту прав і законних інтересів їх учасників. Запропоновано авторське бачення щодо вирішення вказаних проблем. Відсутність чітко сформульованих визначень основних термінів, що лежать в основі інституту відшкодування шкоди, негативним чином позначається на його практичній реалізації, зокрема створюються сприятливі умов для розширеного або, навпаки, звуженого тлумачення змісту цих термінів, що особливо небезпечним є для прав і законних інтересів найманих працівників, як більш вразливої сторони трудових відносин. Чіткість і зрозумілість понять та їх визначень, що застосовуються у законодавстві, забезпечують реалізацію принципів доступності та визначеності права.

Damage compensation is an important institution for restoring justice and protecting the rights and legitimate interests of participants in labor relations. The effectiveness and efficiency of this tool (or means) depends on many conditions and factors, the key place among which is given to the legislative regulation of the material and procedural aspects of the compensation mechanism for the specified damage. Unfortunately, the current state of legislative regulation of compensation for damages in the field of labor law cannot be called normal, since the current Ukrainian labor legislation in this regard contains a number of gaps and other shortcomings. The article, based on the analysis of the norms of the current legislation and the scientific views of scientists, states the presence of a number of significant problems in the legislation that regulates compensation for damages in labor law, which negatively affect the state of legality in the field of labor relations and the effectiveness of protecting the rights and legitimate interests of their participants. The author's vision for solving the specified problems is proposed. The lack of clearly formulated definitions of the main terms underlying the institution of compensation for damages has a negative effect on its practical implementation, in particular, favorable conditions are created for an expanded or, on the contrary, a narrow interpretation of the meaning of these terms, which is especially dangerous for the rights and legitimate interests of employees, as a more vulnerable side of labor relations. Studying the concept of damage in labor law, we have already considered the content of this concept and its characteristic features, as well as the relationship between damage and losses and losses, so we will not return to this issue again. However, at the same time, let us once again note that defining this or that concept, the norm-maker thus outlines the content and most important properties of the corresponding phenomenon, which is a necessary condition for its clear understanding and uniform application. The clarity and comprehensibility of concepts and their definitions used in legislation ensure the implementation of the principles of accessibility and certainty of law.

В статье, опираясь на анализ норм действующего законодательства и научных взглядов ученых, констатировано наличие ряда существенных проблем в законодательстве, которое регламентирует возмещение вреда в трудовом праве, что отрицательным образом сказываются на состоянии законности в сфере трудовых отношений и эффективности защиты прав и законных интересов их участников. Предложено авторское видение решения этих проблем.
Ways to improve labor legislation, the norms of which regulate the issue of compensation for damage
Keywords: трудове законодавство; labor legislation; трудовое законодательство; правове регулювання; legal regulation; правовое регулирование; відшкодування шкоди; reparation; возмещение вреда